The Essence of Pancasila as the Foundation and Ideology of the State: The Values of Pancasila - Siti Zahra Maulida; Murphy Xavier; Mccarty Elliot (Yayasan Adra Karima Hubbi, 2023)
Background. Pancasila is the basic ideology of the Indonesian nation. Pancasila consists of two Sanskrit words: panca which means five and sila which means principle. Purpose. The purpose of this research is that Pancasila itself is a settlement and guidelines for the life of the nation and the state of selirih Indonesian citizens. Method. Data was obtained by giving teacher performance scales, teacher digital literacy, and online learning implementation scales. Results. Here are the five precepts that are in the body of Pancasila, namely: divinity that is the one, fair and civilized humanity, Indonesian unity, democracy led by wisdom and wisdom in representative deliberation, social justice for all Indonesian people. The application of Pancasila must be familiarized from an early age, either through the family or community environment in order to create a safe and peaceful and prosperous environment. In the third precept, it is clear about unity in Indonesia, but there are still many Indonesians who ignore this precept. Conclusion. Of course this case is very detrimental to those who become victims of racism, this action greatly affects a person's mentality for that we as Indonesians must emphasize the values of Pancasila to prevent such cases.